2014
DOI: 10.1007/s10482-014-0220-6
|View full text |Cite
|
Sign up to set email alerts
|

Staurosporine from the endophytic Streptomyces sp. strain CNS-42 acts as a potential biocontrol agent and growth elicitor in cucumber

Abstract: Chinese medicinal plants and their surrounding rhizospheric soil serve as promising sources of actinobacteria. A total of 180 actinobacteria strains were isolated from the rhizosphere soil, leaves, stems, and roots of nine selected plants and have been identified as potential biocontrol agents against Fusarium oxysporum f. sp. cucumerinum. An endophytic strain CNS-42 isolated from Alisma orientale showed the largest zone of inhibition demonstrating a potent effect against F. oxysporum f. sp. cucumerinum and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…10,11 Staurosporines (1-4) showed typical UV-visible spectra similar to those of known indolecarbazoles (supporting information). Figure S2).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…10,11 Staurosporines (1-4) showed typical UV-visible spectra similar to those of known indolecarbazoles (supporting information). Figure S2).…”
mentioning
confidence: 67%
“…10 In our lab, the well-developed HTSS platform has highlighted two significant products, beauvericin and avermectin (Supplementary Table S2), which showed outstanding synergistic activities in combination with a low dosage of KTC against fungal pathogens in vitro. In this study, we report two more molecules 1 and 2 identified with good synergistic antifungal activity.…”
mentioning
confidence: 99%
“…and P. parasitica were inhibited by 47.5, 55.0, 62.5, 77.5 and 90% of the isolates, respectively. Li et al (2014) isolated an endophytic Streptomyces strain CNS-42 isolated from Alisma orientale and showed a potent effect against F. oxysporum f. sp. cucumerinum and a broad antimicrobial activity against bacteria, yeasts and other pathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Root-colonizing Streptomyces have been found to produce a number of antifungal and antimicrobial compounds in situ such as staurosporine, 3-acetonylidene-7-prenylindolin-2-one, diastaphenazine, and antimycin A18 (Yan et al, 2010; Li et al, 2014, 2015; Zhang et al, 2014). These in situ analyses offer a critical lens for beginning to understand bioactive compound production in the natural context of the rhizosphere.…”
Section: Actinomycete Specialized Metabolism In the Rhizospherementioning
confidence: 99%
“…By in large, this association is beneficial for plants as they may receive multiple chemical inputs from actinobacteria, including siderophores, phytohormones, antibiotics, and antifungals that inhibit potential pathogens (Solans et al, 2011; Rungin et al, 2012; Harikrishnan et al, 2014; Li et al, 2014; Zhang et al, 2014). Most studies have examined actinomycete/plant relationships in the context of food crops, some of which are grasses such as wheat, sorghum, rye, maize, and rice (Bressan, 2003; Merzaeva and Shirokikh, 2010; Harikrishnan et al, 2014; Toumatia et al, 2016).…”
Section: Actinomycete Specialized Metabolism In the Rhizospherementioning
confidence: 99%